Analisis Ekonomi Provinsi Jawa Tengah Periode 2015-2019 dengan Metode Indeks Williamson, Tipologi Klassen dan Location Quotient - Raden Annisa Dzikri Nur Hidayah; Amandus Jong Tallo (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2020)
The economy in Central Java has increased from time to time, but the increase does not occur evenly in all districts and cities. This study was conducted to discover the Central Java economic growth conditon in 2019, so as to provide an overview to the community, the government and other institutions of the current economic conditions in the Central Java Province. This study uses data from the Central Statistics Agency (BPS) online site for further processing using the Williamson Index (IW) analysis method, Klassen Typology and Location Quotient (LQ). The GRDP growth rate of Central Java Province in 2019 has decreased compared to 2018, but it is inversely proportional to its per capita income. Central Java Province has the Processing Industry and Education Services activities as the leading business sector, but 13 out of 17 other business sectors are lagging business sectors.